Antibacterial effect of acrylic bone cements loaded with drugs of different action’s mechanism - Morejón Alonso, Lizette; Fernández Torres, Iran; Zayas Tamayo, Ángela M; Ledea Lozano, Oscar Ernesto; Durán Ramos, Ivette; Delgado García-Menocal, José Ángel; Rios-Donato, Nely; Mendizábal, Eduardo (The Journal of Infection in Developing Countries, 2019)
Introduction: Antibiotic-loaded bone cements of poly(methyl methacrylate) are considered as very useful biomaterials for the management of corporal deep osseous infections. However, the high prevalence of resistant germs and polymicrobial infections makes it necessary to search for new formulations of bone cements containing antibiotics for local antibacterial therapy. In this work, bone cements loaded with drugs with different mechanism of action were evaluated to determine its antibacterial effectiveness on Pseudomonas aeruginosa. Methodology: Poly(methyl methacrylate) cements loaded with 10 wt.% of Oleozon®, mixtures of Ciprofloxacin/Meropenem and Ciprofloxacin/Meropenem/Oleozon® were prepared. The in vitro drugs release in water was followed by UV-Vis spectroscopy, and their antibacterial activity against Pseudomonas aeruginosa was evaluated for 11 days using the microdilution method. Results: All the extracts demonstrated an inhibitory effect on the growth of the strain during the whole trial period. Extracts from cement with Oleozon® only presented a total antibacterial inhibitory effect during 20 hours for the extracts taken at day 1 while the extracts from the cements loaded with mixtures of Ciprofloxacin/Meropenem and Ciprofloxacin/Meropenem/Oleozon® showed complete inhibition of the growth of the microorganism, even at 11 days. At the end of the trial period, some of the drugs remained inside the matrices, indicating that they can be released for a longer time in treatments. Conclusions: The results indicated a positive antibacterial effect by the combined used of the two or the three drugs tested against the Gram-negative bacilli Pseudomonas aeruginosa, so these proposal may be a valid alternative to be considered by surgeons.